EFEKTIVITAS SPA KAKI DIABETIK TERHADAP SIRKULASI DARAH PERIFER PADA PASIEN DIABETES MELLITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS WONOKROMO SURABAYA - Affiani, Rahmi; Astuti, Puji (Unusa Press, 2017)
Diabetes mellitus type 2 is often occur and became chronic complication of vascular peripheral disease caused by decreasing peripheral blood circulation. One of therapy to improve peripheral blood circulation is diabetic foot spa, The purpose of this study is to find out the effectiveness of diabetic foot spa towards peripheral blood circulation. Design of this study is Quasy-Experiment. The population were all diabetes mellitus patients type 2 in Public Health Centre Wonokromo Surabaya. Number of sample was 46 person, divided into 2 group, that are treatment group and control group, with 23 person each group, taken by purposive sampling technique. Data analyzed by Mann-Whitney test with α=0.05. Study results on treatment group before giving diabetic foot spa majority (52.2%) of peripheral blood circulation in mild category and for control group mostly (60.9%) have blood circulation in mild category as well. After the foot spa was give to the treatment group, almost entirely (91.3%) had normal peripheral blood circulation, whereas in the control group majority (73.9%) remain mild. Analysis of MannWhitney test P=0.000 < α=0.05, which means diabetic foot spa is effective towards blood circulation. The more frequent perform of diabetic foot spa, the better peripheral blood circulation, it can prevent complications of diabetes mellitus.